FACTORS AFFECTING THE INVESTMENT CLIMATE IN THE JIZZAKH SPECIAL INDUSTRIAL ZONE AND WAYS TO IMPROVE THEM (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
this thesis analyzes the economic, organizational, legal, and infrastructural factors influencing the investment climate in the Jizzakh Special Industrial Zone. The importance of tax and customs benefits, digital management systems, transport and logistics infrastructure, and innovative technologies in increasing the region's investment attractiveness is also highlighted. The thesis develops practical proposals and recommendations for further improving the investment climate.